Antimicrobial Resistance Issue: A Matter of Practice and Capacity to Conduct an Audit - Erni Juwita Nelwan (Acta Medica Indonesiana, 2024)
The World Health Organization released the practical toolkit for antimicrobial stewardship in health-care facilities in low- and middle-income countries in 2019 due to increasing rates of antimicrobial resistance (AMR) causing the diminishing of treatment options and that the available antibiotics seem to no longer work. The introduction of this toolkit indicates the need to be more down-to-earth in combating the problems of antimicrobial resistance. This situation happened because we have taken antibiotics for granted for too long with less awareness, which results in the potential loss of its use and benefits. On the other hand, even though medicine is available, a major issue on the limited access to antibiotics are still reported in many parts of the world.